Parental Expectations and Young People’s Migratory Experiences in Indonesia - Wenty Marina Minza (Jurnal Psikologi, 2017)
Based on a one year qualitative study, this paper examines the migratory aspirations and experiences of non-Chinese young people in Pontianak, West Kalimantan, Indonesia. It is based on two main questions of migration in the context of young people’s education to work transition: 1) How do young people in provincial cities perceive processes of migration? 2) What is the role of intergenerational relations in realizing these aspirations? Living in a provincial city in Indonesia, many of these youth aspire to migrate to larger cities on the Java Island for tertiary education. It is found that apart from the idea that universities in Java are of better quality and diplomas from education institutions in Java provide leverage in the labour market, migrating to Java is also about growing up. Migrating is often linked to ideal notions of adulthood, indicated by independence. Yet, in reality, these aspirations often have to compete with parental expectations of family care and of building interdependent relationships with the family (rather than becoming independent). Thus young people are often constrained by their families in realizing their dreams to seek education in Java and even when they obtain permission to leave, they are expected to come back to Pontianak. This paper will describe the various strategies young people employ to realize their dreams of obtaining education in Java, the decisions made by those who fail to do so, and the choices made by migrants after finishing their education in Java. It will contribute to a body of knowledge on young people’s education to work transitions and how inter-generational dynamics play out in that process.